(untitled) (European Journal of Marketing and Economics, 2026)
The increasing digitalization of markets has profoundly transformed marketing communication strategies, leading many organizations to prioritize inbound and digital approaches. Nevertheless, outbound marketing continues to play a relevant role in influencing consumer purchasing behavior, particularly in contexts where rapid reach, message reinforcement, and brand visibility are critical. This systematic literature review examines how outbound marketing influences consumer purchasing behavior, focusing on its effects on brand perception, purchase intention, trust, and loyalty. Drawing on peer-reviewed studies published between 2019 and 2025 and indexed in Scopus and Web of Science, the review synthesizes empirical evidence on the mechanisms through which outbound communication affects consumer decision-making. The findings indicate that message clarity, controlled repetition, channel–audience congruence, and perceived credibility are key determinants of outbound marketing effectiveness. Moreover, cultural and contextual factors significantly moderate consumer responses, highlighting the need for adaptive and ethical communication strategies. The study contributes to marketing literature by integrating outbound marketing effects with established consumer behavior theories and offers practical implications for managers operating in increasingly competitive and digitally saturated markets.